Enterprise mobility: concept and examples. (12th May 2004) - Barnes, Stuart J.
Although the literature on wireless applications has predominantly focused on business-to-consumer markets, following the patterns in the media and e-commerce research, it is now becoming clear that mobile networking will provide a tremendous impetus to the development of other strategic applications for businesses. This paper explores this emerging area of wireless applications in the business, focusing specifically on enterprise mobility. It aims to provide a basic background to conceptual ideas of enterprise mobility, and a framework for understanding the development of enterprise mobility in organisations. Moreover, the paper also begins to apply these conceptual ideas in a number of original case studies. The paper rounds off with a summary and some conclusions regarding the future of enterprise mobility.